Accumulation and phytoextraction potential of heavy metals of Enhalus acoroides in the coastal waters of Lamongan, Java, Indonesia - Defri Yona; Syarifah Hikmah Julinda Sari; Safitri, Ruli Hikmah (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study quantified the concentration of heavy metals Cd and Cu in Enhalus acoroides from shallow seagrass habitat in the northern coastal waters of Lamongan, Indonesia. The objective of this study was to determine the concentration of these metals in different parts of seagrass E. acoroides and to assess their biomonitoring potential of heavy metals pollution in coastal areas. Heavy metal contents in the sediments, roots and leaves of E. acoroides were determined by Flame Atomic Absorption Spectrometry from four sampling sites. The results showed that the concentrations of Cu were significantly higher than the concentrations of Cd in both sediments and seagrass tissues in all stations. The concentrations of Cu were found in slightly similar values in the sediments, roots and leaves. On the other hand, the concentrations of Cd were higher in the sediments than in the roots and leaves of E. acoroides. In addition, Bioconcentration Factor (BCF) of Cu in E. acoroides was two times higher than BCF of Cd (BCFCu = 1.09; BCFCd = 0.49). In contrast, Translocation Factor (TF) of Cu was lower than TF of Cd that was 0.65 and 1.05, respectively. According to BCF and TF values, E. acoroides can be considered to have the ability to perform phytoextraction process especially Cd because E. acoroides was able to restrict its absorption of Cd from the environment (BCF < 1) and once it is absorbed, the plant has the ability to transfer it to the other body parts (TF > 1).